Oxygen Reduction Reaction Mechanism on the Square Paddle-Wheel Cage Site of TM-BTC (TM=Mn, Fe, Cu) Metal-Organic Framework - Ahmad Nuruddin; Adhitya Gandaryus Saputro; Syauqi Abdurrahman Abrori; Arifin Luthfi Maulana; Virgiawan Listanto Rahagung; Mohammad Kemal Agusta; Fadjar Fathurrahman; Amrina Mustaqim; Hermawan Kresno Dipojono (Journal of Mathematical and Fundamental Sciences, 2022)
Our study examined the mechanism of oxygen reduction reactions (ORR) at the square paddle-wheel cage active site of TM-BTC metal-organic frameworks (MOFs), where TM is a transition metal, Mn, Fe, or Cu. We used a combination of density functional theory (DFT) and microkinetic calculations to investigate this mechanism. By using a small cluster for modeling the TM-BTC active site structure, we successfully reproduced the experimental trend of ORR activity in the TM-BTC systems: Mn-BTC > Fe-BTC > Cu-BTC. We also found that the unusual ORR activity trend in experiments for Mn and Fe systems originates from the strength of OH adsorption on these systems. The Mn-BTC system exhibits higher ORR activity than the Fe-BTC system due to its weaker adsorption of OH groups. A very strong OH adsorption makes the final OH reduction step sluggish, hence hindering the ORR process.